The Met Office Unified Model Global Atmosphere 4.0 and JULES Global Land 4.0 configurations - Walters, D. N.; Williams, K. D.; Boutle, I. A.; Bushell, A. C.; Edwards, J. M.; Field, P. R.; Lock, A. P.; Morcrette, C. J.; Stratton, R. A.; Wilkinson, J. M.; Willett, M. R.; Bellouin, N.; et al. (Geoscientific model development, 2014)
We describe Global Atmosphere 4.0 (GA4.0) and Global Land 4.0 (GL4.0): configurations of the Met Office Unified Model and JULES (Joint UK Land Environment Simulator) community land surface model developed for use in global and regional climate research and weather prediction activities. GA4.0 and GL4.0 are based on the previous GA3.0 and GL3.0 configurations, with the inclusion of developments made by the Met Office and its collaborators during its annual development cycle. This paper provides a comprehensive technical and scientific description of GA4.0 and GL4.0 as well as details of how these differ from their predecessors. We also present the results of some initial evaluations of their performance. Overall, performance is comparable with that of GA3.0/GL3.0; the updated configurations include improvements to the science of several parametrisation schemes, however, and will form a baseline for further ongoing development.